Exome sequencing in families with severe mental illness identifies novel and rare variants in genes implicated in Mendelian neuropsychiatric syndromes. Issue 1 (12th December 2018) - Ganesh, Suhas; Ahmed P., Husayn; Nadella, Ravi K.; More, Ravi P.; Seshadri, Manasa; Viswanath, Biju; Rao, Mahendra; Jain, Sanjeev; ,; Mukherjee, Odity
Abstract : Aim: Severe mental illnesses (SMI), such as bipolar disorder and schizophrenia, are highly heritable, and have a complex pattern of inheritance. Genome‐wide association studies detect a part of the heritability, which can be attributed to common genetic variation. Examination of rare variants with next‐generation sequencing may add to the understanding of the genetic architecture of SMI. Methods: We analyzed 32 ill subjects from eight multiplex families and 33 healthy individuals using whole‐exome sequencing. Prioritized variants were selected by a three‐step filtering process, which included: deleteriousness by five in silico algorithms; sharing within families by affected individuals; rarity in South Asian sample estimated using the Exome Aggregation Consortium data; and complete absence of these variants in control individuals from the same gene pool. Results: We identified 42 rare, non‐synonymous deleterious variants (~5 per pedigree) in this study. None of the variants were shared across families, indicating a 'private' mutational profile. Twenty (47.6%) of the variant harboring genes were previously reported to contribute to the risk of diverse neuropsychiatric syndromes, nine (21.4%) of which were of Mendelian inheritance. These included genes carrying novel deleterious variants, such as the GRM1 gene implicated in spinocerebellar ataxia 44 and the NIPBL gene implicated in Cornelia de Lange syndrome. Conclusion: Next‐generation sequencing approaches in family‐based studies are useful to identify novel and rare variants in genes for complex disorders like SMI. The findings of the study suggest a potential phenotypic burden of rare variants in Mendelian disease genes, indicating pleiotropic effects in the etiology of SMI.